2014
DOI: 10.1038/ncomms6706
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of complex hydride perovskite materials

Abstract: Perovskite materials host an incredible variety of functionalities. Although the lightest element, hydrogen, is rarely encountered in oxide perovskite lattices, it was recently observed as the hydride anion H À , substituting for the oxide anion in BaTiO 3 . Here we present a series of 30 new complex hydride perovskite-type materials, based on the non-spherical tetrahydroborate anion BH 4 À and new synthesis protocols involving rare-earth elements. Photophysical, electronic and hydrogen storage properties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
221
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(237 citation statements)
references
References 44 publications
14
221
1
Order By: Relevance
“…- [85]. Structural dynamics on the anion site are systematically introduced to the perovskite structure type, and anion substitution, where BH 4 -is partially replaced by the heavier halides, Cl -, Br -or I -, readily occurs, contributing to a vast structural flexibility and compositional diversity.…”
Section: New Properties Of Metal Borohydrides-towards Multi-functionamentioning
confidence: 99%
“…- [85]. Structural dynamics on the anion site are systematically introduced to the perovskite structure type, and anion substitution, where BH 4 -is partially replaced by the heavier halides, Cl -, Br -or I -, readily occurs, contributing to a vast structural flexibility and compositional diversity.…”
Section: New Properties Of Metal Borohydrides-towards Multi-functionamentioning
confidence: 99%
“…Li-containing RE borohydrides are also considered as solid state electrolytes for new battery applications, due to their high Li-ion conductivities [20][21][22][23]. RE borohydrides have shown novel properties such as luminescence, and a magnetocaloric effect has also been recently published [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Semi-empirical chemical concepts combining the stabilities of the less stable and more stable borohydrides [2], for instance, have given way to more profound concepts that exploit different kinds of weak interaction [3]. Recently, we reported on a large family of mixed-metal borohydrides crystallizing in the perovskite structure type, the latter being a prime example of functional materials design [4]. As a very stable structure type, the perovskite form allows one to study the behavior of a large range of different metals in a borohydride environment, but also to apply an immense toolbox developed throughout decades of metal-oxide perovskite design.…”
Section: Introductionmentioning
confidence: 99%
“…A logical further step is to explore anion-mixing on the ligand site. It was shown that the borohydride perovskite host readily takes up halide anions on the borohydride site [4]. In this context, it comes to mind to test the nitrogen-based hydrogen molecules, which are currently being vigorously investigated as means to tailor hydrogen release temperatures [3].…”
Section: Introductionmentioning
confidence: 99%